Microencapsulação por atomização do suco misto de acerola e ciriguela probiótico - Souza, Michelle Maria Barreto de (2019)
Atomization microencapsulation has been widely used in the maintenance of probiotic microrganisms in fruit juice. However, no research has focused so far on the use of various probiotic microrganisms in mixed beverage. The encapsulating agent is one of the most important operating parameters that imply different product properties. The objectives of this work was to develop new probiotic product of non-dairy origin by spray dryer microencapsulation of mixed acerola and ciriguela juice containing Lactobacillus rhamnosus LPAA 01, Lactobacillus casei LPAA 02 and Lactobacillus plantarum LPAA 03, evaluate the effect of maltodextrin with different equivalent dextrose (DE) on physicochemical, physical, sensory and microbial viability properties, as well as to select the best DE to characterize the microcapsules in terms of in vitro bioaccessibility of phenolic compounds and antioxidant activity, identify resistance of the three species of Lactobacillus multiplex PCR and other physical, chemical and physicochemical properties. Microencapsulation was performed in a mini-spray dryer in laboratory scale with air inlet temperature of 140 °C, feed rate of 0.60 L/h and 10% of maltodextrin DE 5, 10 and 15. The hydrolyzation degree of maltodextrin interfered in the cell viability, physicochemical and physical parameters, observing the best results in lower DE values. Microbiological analyzes indicated that the powders presented satisfactory conditions of hygiene practices, being suitable for human consumption. The reconstituted nectars of mixed juice acerola and ciriguela powder probiotic did not show any significant difference between the samples by check-all-that-apply (CATA) and acceptance tests. However, evaluating together the results of the physicochemical, physical, sensory and cell viability analyzes point to maltodextrin DE 5 as a promising material for probiotic bacteria microencapsulated in fruit juices, reason for choosing to continue research. Microcapsules obtained with maltodextrin DE 5 presented good physical-chemical, physical and chemical parameters. Each specific primer pair showed unique amplification, confirming the survival of Lactobacillus, L. casei being able to survive in greater quantity the microencapsulation by spray dryer under the conditions applied in this study. Phenolic levels, except for gallic acid decreased after exposure to simulated gastric conditions as well as antioxidant activity. Even so, powder juice showed high bioactive properties with potential use for industry.